PENENTUAN PERINGKAT PELANGGAN TERBAIK MENGGUNAKAN METODE RANK ORDER CENTROID DAN WEIGHTED PRODUCT (STUDI KASUS ONESNET) - Mugiarso; Rasim (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2023)
This study addresses the problem faced by Onesnet in its environment, which is how to provide discounts or rewards to customers who have not received them before. This is due to the increasing competition in the internet installation service industry. The aim of this research is to determine the best customers in order to maintain customer loyalty in the increasingly competitive industry. The Weighted Product method is used as a decision-making technique by multiplying the ratings of each connected attribute, where the ratings of each attribute must be exponentiated with the corresponding attribute weight. The data used in this research comes from interviews and observations at Onesnet, which will be processed using the Rank Order Centroid method for weighting and Weighted Product method to evaluate and make a decision. The result of this study is the most loyal customer who becomes the best customer with a value of 0.14578.